PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR PKn SISWA KELAS V MI AL-WASLIAH SUNGAI MAJO KECAMATAN KUBU KABUPATEN ROKAN HILIR - ', Kasrita Kasrita; ', Lazim. N Lazim. N; ', Zulkifli Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : This study starts from the low PKN student learning outcomes, with anaverage value of 65.5 class. While the value of minimum completeness criteria(KKM) PKN is 68 This research is a class action (PTK). Aiming to improvestudent learning outcomes Civics class V MI Al Wasliah River Majo Kubu districtof Rokan Hilir. Formulation of the problem: Is the application of Role Playinglearning model to improve learning outcomes of students Civics class V MI Al-Wasliah Majo River Kubu district of Rokan Hilir. Student learning outcomesbefore action for 65.55 with less category, while after the action on the first cycleof 74.25 with enough categories and the second cycle of 82.25 with bothcategories. From this data it can be seen comparison of improving studentlearning outcomes from a base score of 8.7 while kesiklus one of two kesiklusbase score of 19.7. Activities that teachers do in the first cycle is the average of62.5%, while the activity of the teachers in the second cycle with an average of77.08%. Activities of the student in the first cycle with an average of 53.33%.While the activities of students in the second cycle is the average of 72.91%.These results prove that the application of Role Playing learning model toimprove learning outcomes of students Civics class V MI Al-Wasliah Majo RiverKubu district of Rokan Hilir.Keywords: Role Playing, PKn Learning Outcomes